Microvascular dysfunction in a murine model of Alzheimer’s disease using intravital microscopy - Sidsworth, Danielle; Tregobov, Noah; Jamieson, Colin; Reutens-Hernandez, Jennifer; Yoon, Joshua; Payne, Geoffrey W.; Sellers, Stephanie L. (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a complex neurocognitive disorder. Early theories of AD sought to identify a single unifying explanation underlying AD pathogenesis; however, evolving evidence suggests it is a multifactorial, systemic disease, involving multiple systems. Of note, vascular dysfunction, encompassing both cerebral and peripheral circulation, has been implicated in AD pathogenesis. This pilot study used intravital microscopy to assess differences in responsiveness of gluteal muscle arterioles between a transgenic AD mouse model (APP/PS1; Tg) and wild-type (C57BL/6; WT) mice to further elucidate the role of vascular dysfunction in AD. Arteriole diameters were measured in response to acetylcholine (10–9 to 10–5 M), phenylephrine (10–9 to 10–5 M), histamine (10–9 to 10–4 M) and compound 48/80 (10–9 to 10–3 M). Tg mice demonstrated a trend toward reduced vasodilatory response to acetylcholine with a significant difference at 10–5 M (36.91 vs. 69.55%: p = 0.0107) when compared to WT. No significant differences were observed with histamine, compound 48/80 or phenylephrine; however, a trend toward reduced vasoconstriction to phenylephrine was observed in Tg mice at higher concentrations. Mean net diameter change (resting to maximum) also differed significantly (p = 0.0365) between WT (19.11 μm) and Tg mice (11.13 μm). These findings suggest reduced vascular responsiveness may contribute to the systemic vascular deficits previously observed in AD models. Future research using diverse models and broader variables could further elucidate peripheral vascular dysfunction’s role in AD pathogenesis, including its impact on motor symptoms and disease progression. Such insights may inform the development of vascular-targeted therapeutic strategies.